2011
DOI: 10.31421/ijhs/17/1-2./937
|View full text |Cite
|
Sign up to set email alerts
|

New sweet cherry cultivars in intensive plantings

Abstract: The study took place in the largest sweet cherry plantation in West Hungary. The purpose has been the identification of those varieties, which will be suitable for intense cultivation, early fruiting and excellent fruit quality, moreover, the selection of the optimal phytotechnical procedures. At the same time, scion-rootstock combinations have been tested also from the point of view of growing intensity and fruiting in high-density plantation. The dense planting is induced to start fruiting early and yield re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Based on Vaszily & Gonda (2010) researches planting orchard with high density on Prunus mahaleb rootstock is achievable, nevertheless special pruning policy recommended for each cultivar to maintain high yield and fruit quality for a longer period. Szabó et al (2011a) also confirmed this state proving that intensive growing technology can be performed also on growth inducing rootstocks, but dwarfing rootstocks (PHL-A, Gisela 6) can provide earlier cropping and adequate fruit size at the same time.…”
Section: Introductionmentioning
confidence: 57%
“…Based on Vaszily & Gonda (2010) researches planting orchard with high density on Prunus mahaleb rootstock is achievable, nevertheless special pruning policy recommended for each cultivar to maintain high yield and fruit quality for a longer period. Szabó et al (2011a) also confirmed this state proving that intensive growing technology can be performed also on growth inducing rootstocks, but dwarfing rootstocks (PHL-A, Gisela 6) can provide earlier cropping and adequate fruit size at the same time.…”
Section: Introductionmentioning
confidence: 57%
“…A cseresznye minőségét leginkább a gyümölcs mérete, színe, húskeménysége, aromája határozza meg (ESTI et al, 2002;SIMON et al, 2004;USENIK et al, 2005;MUSKOVICS et al, 2006;SZABÓ et al, 2011;GABRIELE et al, 2013;CSIHON et al, 2018). Emellett táplálkozás-élettani szempontból fontos értékmérő a tápelem-, a fenolos vegyület-, az antocianin-, és az antioxidáns-tartalma is (WANG at el., 1997;KIM et al, 2005;JAKOBEK at el., 2007).…”
Section: Bevezetésunclassified